Thermodynamic Modeling and Activity Analysis of Bi-In-Sn Ternary Liquid Alloys at High Temperatures - Sah, Sanjay Kumar; Koirala, Ishwar (Journal of Institute of Science and Technology, 2024)
The activities of each component metal, i.e., Bi, In, and Sn in Bi-In-Sn at 1000 K, were calculated for ternary liquid alloys, which are lead-free, applying the molecular interaction volume model (MIVM). The predicted values of the activity of the component Bi and the associated experimental data were analyzed for Bi-In-Sn at 1000 K. Between the theory and experiment, there was a significant amount of agreement. Both negative and positive deviations of Bi activity, the negative activity deviation of In, and the positive activity deviation of Sn from ideal Raoult's law have been observed in Bi-In-Sn liquid alloys at 1000 K. In addition, the partial molar Gibbs free energy (Δ¯(GBi) of Bi in Bi-In-Sn alloys at 1025 K was also calculated and compared with the available experimental data, which also shows a reasonable agreement.